Development of Islamic Boarding School Management As An Agent of Change in Improving the Quality of Education in the Modern Era - Rizqi, Anwar; Rahmat Bin Abdullah (Medina-te : Jurnal Studi Islam, 2026)
This study aims to analyse the development of pesantren management as an effort to improve the quality of education and sustainability of institutions in the modern era. The main focus of this study is how pesantren can act as agents of change through effective and adaptive educational management in the face of globalisation challenges. This study uses the Systematic Literature Review (SLR) method by analysing various literature sources, including books, journal articles, and relevant research reports. The collected data was analysed through the stages of identification, selection, classification, and synthesis of findings to produce a comprehensive picture of pesantren management. The results show that the development of pesantren management, which includes planning, organising, implementing, and supervising, can improve the effectiveness of education, produce competent graduates, and maintain the relevance of traditional values to modern demands. Thus, pesantren not only function as traditional Islamic educational institutions, but also as agents of change that contribute to the development of society and the nation.